Flattening the curve: manual method for corneal allogenic intrastromal ring segment implantation. Issue 11 (November 2021) - Parker, Jack S.; Dockery, Philip W.; Parker, John S.
Abstract : Corneal allogenic ring segments are semicircular pieces of donor corneal stroma that may be surgically implanted to flatten keratoconic corneas. Conventionally, these donor segments are inserted into channels created using femtosecond laser dissection. However, access to femtosecond technology is not universal. In this study, an alternate, manual technique for channel creation, which is femtosecond laser independent, is described.